Humanizing Digital Marketing: The Role of ChatGPT in Human Resource Management Training Programs - Rachman, Andy; Ausat, Abu Muna Almaududi; Rijal, Syamsu (ADMAN: Journal of Contemporary Administration and Management, 2024)
Successful digital marketing is not just about broadcasting messages to consumers but also about building meaningful relationships with them. This demands a more humanistic approach in digital marketing. This research aims to explore the role of ChatGPT in humanizing digital marketing, with a specific focus on how this technology can be utilized in human resource management training programs. The research method employed is a qualitative literature review using data obtained from Google Scholar spanning from 2016 to 2023. Qualitative approach was chosen to allow for in-depth analysis of relevant literature on the research topic, involving a better understanding of concepts, theories, and findings already existing in the related scholarly literature. The study findings indicate that in rapidly evolving digital marketing, humanization is key to building strong customer relationships. The role of ChatGPT in human resource management training programs is crucial to reinforce humanization in digital marketing strategies. By leveraging ChatGPT, marketing professionals can create more personalized and relevant experiences for their audience, while also opening opportunities to enhance marketing strategy efficiency.